The Influence of Leader-Member Exchange and Employee Empowerment on Job Satisfaction Mediated by Knowledge Sharing - Nurahman, Ikhsan; Al-Kindi, Muhammad Artova; Indrianto, Anggraeni Pratama (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2024)
This research aims to explore the influence of Leader-Member Exchange (LMX) and Employee Empowerment on employee job, with knowledge sharing as a mediating factor. Using a descriptive quantitative approach, data were collected from 99 employees at PT XYZ Tutoring Institute through questionnaires and interviews. The data were analyzed using Partial Least Square (PLS) and Smart PLS V.3 software to ensure validity and reliability. The findings reveal that both LMX and Employee Empowerment significantly enhance job satisfaction through improved knowledge-sharing practices. These results highlight the importance of fostering strong relationships between leaders and employees, as well as empowering employees to boost organizational performance. In conclusion, this research contributes to a better understanding of how internal organizational dynamics, specifically LMX and Employee Empowerment, can influence employee performance and job satisfaction.